2015
DOI: 10.1007/s13760-015-0453-9
|View full text |Cite
|
Sign up to set email alerts
|

Galantamine improves sleep quality in patients with dementia

Abstract: The purpose of the study was to evaluate the influences of cholinesterase inhibitors on sleep pattern and sleep disturbance. A total of 87 mild to moderate stage dementia patients who were not on cholinesterase enzyme inhibitor and memantine treatment were included in the study. The dementia patients were treated with donepezil, galantamine or rivastigmine, depending on the preference of the clinician. Fifty-five dementia patients (63.2 %) completed the study. Twenty-three elderly subjects, who had normal cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“… 147 For example, insomnia and nightmares are frequent side effects of donezepil 148 when it is administered at night but produces a slight improvement in sleep quality when administered in the morning. 149 Galantamine has the best profile regarding sleep and may be the first choice of cholinesterase inhibitor in mild-to-moderate dementia patients in terms of improving sleep quality. 149 151 One case of rivastigmine induced REM behavior disorder (RBD) has been reported.…”
Section: Treatment Of Ad: Effect On Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“… 147 For example, insomnia and nightmares are frequent side effects of donezepil 148 when it is administered at night but produces a slight improvement in sleep quality when administered in the morning. 149 Galantamine has the best profile regarding sleep and may be the first choice of cholinesterase inhibitor in mild-to-moderate dementia patients in terms of improving sleep quality. 149 151 One case of rivastigmine induced REM behavior disorder (RBD) has been reported.…”
Section: Treatment Of Ad: Effect On Sleepmentioning
confidence: 99%
“… 149 Galantamine has the best profile regarding sleep and may be the first choice of cholinesterase inhibitor in mild-to-moderate dementia patients in terms of improving sleep quality. 149 151 One case of rivastigmine induced REM behavior disorder (RBD) has been reported. 152 However, it seems that donezepil and rivastigmine might be effective to treat RBD.…”
Section: Treatment Of Ad: Effect On Sleepmentioning
confidence: 99%
“…The effectiveness of a cholinesterase inhibitor (ChEI) for sleep disturbance in AD is unclear. One observational study showed that galantamine improved sleep disturbance in AD and mixed type dementia, while donepezil did not do so [ 32 ]. ChEIs are thought to increase regional cerebral blood flow mainly in the frontal lobe [ 33 ], but a functional MRI study showed that galantamine increased functional connectivity in the posterior cingulate cortex and precuneus [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effect of cholinesterase inhibitors using PSQI on sleep was investigated in a study conducted by Naharci et al They found a superior decline in posttreatment PSQI score in patients using galantamine, although not statistically significant, in comparison with other groups of patients (donepezil, rivastigmine and controls) and they advised to use galantamine in dementia as a first-option medication [14]. In a randomized double-blind trial, donepezil and galantamine did not have deleterious effects on sleep, furthermore galantamine was found to be slightly more beneficial than of donepezil in terms of sleep quality [7].…”
Section: Discussionmentioning
confidence: 99%